PANCASILA AS A GLOBAL ETHICS OF MULTICULTURAL - Kaelan Kaelan (Sadra International Institute, 2023)
In a scientific study conducted by George McTurner Kahin of Cornell University, philosopher Bertrand Russell of England, and Dahm, it is explained that Pancasila, developed by the founder of the nation and state of Indonesia, is an interdisciplinary synthesis betweenliberalism, marxism, and religious values (in this case Islam). The position of the principal Pancasila consists of two things, namelyas the basis of state (philosofische groundslag) and the nation’s way of life, which can also be a universal worldview. In the formulation of Pancasila, Sukarno said that Pancasila is ‘weltanchauung’ whose meaning is ‘worldview’, or it can be interpreted that the Pancasila has principles and values of morality that are based on religion, and it is very important to be appointed as a global ethic in the face of the multicultural life. The essence of Pancasila: the deity, humanity, unity, democracy, and justice, is a universal philosophical principle. This means that the essential values of Pancasila are not only for the Indonesian nation but can be realized by the entire nation in the world in creating a society that is prosperous, devout, civilized, united, equal, and just. This writing will discuss Pancasila as a worldview and its relevance as a global ethics of multiculturalism in the world today. This writing emphasizes the philosophical views of society, the nation, and human beings as the primary supporters of the state. It provides us with perspective and characterizes Pancasila philosophy as an additional viewpoint alongside other philosophical views in the world, such as liberalism, individualism, socialism, communism, secularism, pragmatism, materialism, and religious fundamentalism.